Resistência do solo com cultivo de erva-mate e plantas de cobertura - França, Jéssica Silveira (2021)
Improper management in production systems can lead to soil degradation, by erosion, loss of organic carbon and even by the compaction process, which is one of the main ways of compromising its structure. The soil susceptibility to degradation is related to its structural strength. Given the constant degradation of soils caused mainly by improper use and management, it is necessary to adopt management practices in the productive systems that preserve the multifunctionality of the soil, aiming its conservation, in order to avoid degradation and loss of production capacity. The use of cover crops is a widely used management strategy to maintain productive capacity in agricultural areas, especially for their benefits in fertility and possible improvement in the soil physical quality. However, in areas of perennial plant cultivation, such as yerba mate, which comprises a system without soil mobilization and reduced traffic operations, the indication for the use of cover crops is still limited. The objective of the study was to evaluate whether the use of cover crops intercropped with yerba mate (Ilex paraguariensis) in an area without soil mobilization modifies the physical-mechanical parameters that provide greater soil resistance. The experiment was implanted in 2014, and consisted in the intercropping of cover crops with yerba mate, in a randomized block design, with four blocks and four treatments: forage peanut (AM.F), black oat + vetch and cowpea (AP.E.F), perennial soybean (SP) and spontaneous vegetation (VE). In the year of 2019, samples with preserved structure were collected in the layers 1-4 cm and 10-14 cm to determine physical-mechanical properties and soil air permeability. Soil organic carbon content was determined for correlation analysis with compressibility properties and shear strength parameters. The distribution of the size of the stable aggregates in water was evaluated only for the 1-4 cm layer. The soil resistance to penetration was determined in the field up to 30 cm deep. The use of cover crops did not cause changes in physical and mechanical parameters in relation to spontaneous vegetation. It is worth noting that the cover crops have been established for five years, a time that may be insufficient to promote significant changes in these parameters. The values of the DMP and DMG indexes were high (> 2 mm) for all the evaluated cover crops, indicating structural stability of the aggregates in this system. High strength values were observed through the mechanical parameters. This greater soil resistance did not compromise its functionality, as observed by the air permeability assessment, which resulted in appropriate values for all treatments, in the two evaluated layers. In this system, cover crops and spontaneous vegetation provided improvements in the soil, mainly related to its structure. With this, more adequate structural conditions are established to favor the production of the perennial culture. Thus, the functionality of the soil is maintained in systems without mobilization associated with the use of vegetation cover, allowing to reconcile production with environmental preservation.